Workshop Mix Media Print (Cetak Tinggi dan Kolase Digital) Seni Kaligrafi Arab di The Park Mall Sukoharjo - Sigit Purnomo Adi; Pande Made Sukerta; Martinus Dwi Marianto; Sri Hadi; Fuad Safrudin (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2023)
Arabic calligraphy can be an art medium for da'wah, it can also be an aesthetic medium at home or in a mosque or otherwise. The arts-based activities are no exception. One of them is the art of Arabic calligraphy, the art of Arabic calligraphy itself is taught from elementary to high school based on Islamic schools. Calligraphy is indeed very interesting to teach, because it can be used as a medium to instill an attitude of religiosity and devotion to God Almighty through the media of art. Based on the experience that has been experienced by the author both as a creator of Arabic calligraphy works and also as a graphic artist, the author and the PKM TEAM are trying to find partners, especially schools that are suitable to be trained in the creation of calligraphy works by combining graphic art and collage techniques. The author considers the importance of inculcating religiosity among junior high school students with a touch of art and entrepreneurship. The purpose of this community service (PKM) is to train and assist students of SMP Muhammadiyah 9 Jaten, Karanganyar, especially in Arabic calligraphy art lessons so that they can progress and develop. The second is so that the work produced is not only an educational medium but can be a business opportunity in the arts, especially calligraphy. So that the resulting calligraphy works can be sold at art exhibitions, online stores and others. The training process went through several stages, including 1. Problem identification stage at the location 2. Training and mentoring stage at The Park Mall, Sukoharjo 3. Participants evaluation stage and the work produced.